Effect of Scaling and Root Planing on Detection of Tannerella forsythia in Chronic Periodontitis. (22nd December 2013) - Wadhwani, Ritesh B.; Chaudhary, Minal S.; Tharani, Dipti A.; Chandak, Shweta A.
Abstract : Aim . This study was aimed to determine the prevalence of Tannerella forsythia in subgingival plaque samples of chronic periodontitis patients having different level of periodontal destruction and to assess the effect of scaling and root planing (SRP) on prevalence of T. forsythia . Materials and Methods . Study included 3 groups: group 1 were healthy individuals, group 2 had periodontitis with probing depth ≤ 5 mm, and group 3 had periodontitis with probing depth > 5 mm. Subjects in groups 2 and 3 exhibited both healthy and diseased periodontal sites. Prevalence of T. forsythia was determined using polymerase chain reaction. Subjects in groups 2 and 3 received SRP and were reevaluated three months after SRP. Results . T. forsythia was not detected in group 1. It was found in diseased sites in 40% and 73.33% of patients from groups 2 and 3, respectively. It was also found in healthy sites in 6.67% and 13.33% of patients from groups 2 and 3, respectively. The detection frequency of T. forsythia after SRP was 6.67% and 13.33% in groups 2 and 3, respectively. Conclusion . The results indicate a possible association between periodontal disease and presence of T. forsythia . Also, the detection frequency of T. forsythia was reduced after SRP.